Overcoming your alcohol or drug problem : effective recovery strategies : therapist guide - Daley, Dennis C. (Treatments that work., 2006)
Designed to accompany the ""Overcoming Your Alcohol or Drug Problem Workbook"", this guide provides clinicians with strategies for working with substance use disorders by focusing on specific issues involved in both stopping substance abuse and changing behaviours or lifestyle asepcts that contribute to continued substance abuse.